Lessons learned on food security in the Yemen crisis - Kurdi, Sikandra (Pontifical Academy of Sciences, 2024)
From the wealthy kingdom the Queen of Sheba to the “Arabia Felix” on Roman maps, Yemen was historically known as a rich, fertile, and fortunate land. In the late twentieth century, however, Yemen’s economic growth was stalled by a weak central government and complex tribal patronage system. Unlike other neighboring Gulf states, Yemen has very limited oil reserves, and remittance income from migrants became a major source of income, displacing investment in agricultural production. Coupled with high population growth, Yemen increasingly became dependent on imported food supplies. Poverty and malnutrition rates were also high. In 2013, 46.5% of children under 5 in Yemen were stunted and 16.3% suffered from acute malnutrition (Yemen DHS 2013). These development challenges in Yemen exploded into a humanitarian emergency with the beginning of the ongoing war in 2015.